(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article explores a paradigm shift toward no-stress methods for assessing reading comprehension. We will move beyond the limitations of traditional exams to discover authentic, engaging, and low-pressure techniques that provide richer, more meaningful insights into what a student truly grasps and connects with. From interactive conversations and creative projects to observation and digital tools, these methods prioritize the joy of understanding over the fear of evaluation. The goal is not to eliminate assessment, but to redesign it as a natural, supportive, and even enjoyable part of the learning journey—one that informs instruction and empowers readers rather than intimidating them. Join us as we explore practical, evidence-based strategies that assess comprehension by inviting students to show what they know in ways that feel natural, collaborative, and stress-free.